THE EFFECT OF PROVIDING HEALTH EDUCATION ABOUT MENSTRUATION ON READINESS OF STUDENTS TO FACE MENARCHE - Khairunnsa; Sri Ratna Ningsih (Universitas Karya Husada Semarang, 2025)
Menarche is the onset of menstruation, typically occurring between the ages of 10 and 16. Adolescents who are unprepared to face menarche may develop feelings of rejection toward this physiological process, viewing menstruation as something harsh and threatening. Adequate education and information about menstruation are crucial for female students to be well-prepared for menarche. This study aims to assess the effect of health education on menstruation on female students' readiness to face menarche. The research employed a cross-sectional method with a pre-experimental design using a one-group pre-test and post-test approach. The sampling technique used was purposive sampling. The data analysis was conducted using the nonparametric Wilcoxon matched pairs test. The results showed a significant improvement in students' readiness after receiving health education, with a p-value of 0.000 (0.05). The study concludes that health education significantly enhances students' readiness to face menarche. It is recommended that schools collaborate with healthcare professionals to provide menstruation education, ensuring that students are better prepared for menarche.